Social Deixis in the Novel â€œGadis Pesisirâ€ By Nunuk Y. Kusmiana Pragmatic Review - Ulina Beru Ginting, Sri; Hayati Maulidiah, Rina; Nisa, Khairun (Devotion : Journal of Community Service, 2022)
This study aims to describe the form of social deixis in the novel Gadis Pesisir by Nunuk Y. Kusmiana with a pragmatic review. The research approach used in this study uses a qualitative approach with descriptive analysis techniques. This research is a qualitative research with a descriptive method that examines social deixis in an Indonesian novel with a pragmatic review. The data collection technique used is literature study. The data sources in this study are primary data and secondary data, the primary data used researchers in research are sentences or paragraphs that have social deixis in the novel "Girl Pesisir " by Nunuk Y. Kusmiana, secondary data for compiling this research is in the form of several theory books. The results show that there are three hundred and eighty-five social deixis in the form of words and phrases. The results show that social deixis in the form of words is one hundred and forty-two while the social deixis in the form of phrases is two hundred and forty-three. Besides the researchers also found Â two hundred and seventy-four in the form of maintaining language manners, sixty-seven differentiators of social identity, thirty-five differentiators of social level, and eleven making sentences effective.